Insights into breeding history, hotspot regions of selection, and untapped allelic diversity for bread wheat breeding. (4th November 2022) - Lehnert, Heike; Berner, Thomas; Lang, Daniel; Beier, Sebastian; Stein, Nils; Himmelbach, Axel; Kilian, Benjamin; Keilwagen, Jens
SUMMARY: Breeding has increasingly altered the genetics of crop plants since the domestication of their wild progenitors. It is postulated that the genetic diversity of elite wheat breeding pools is too narrow to cope with future challenges. In contrast, plant genetic resources (PGRs) of wheat stored in genebanks are valuable sources of unexploited genetic diversity. Therefore, to ensure breeding progress in the future, it is of prime importance to identify the useful allelic diversity available in PGRs and to transfer it into elite breeding pools. Here, a diverse collection consisting of modern winter wheat cultivars and genebank accessions was investigated based on reduced‐representation genomic sequencing and an iSelect single nucleotide polymorphism (SNP) chip array. Analyses of these datasets provided detailed insights into population structure, levels of genetic diversity, sources of new allelic diversity, and genomic regions affected by breeding activities. We identified 57 regions representing genomic signatures of selection and 827 regions representing private alleles associated exclusively with genebank accessions. The presence of known functional wheat genes, quantitative trait loci, and large chromosomal modifications, i.e., introgressions from wheat wild relatives, provided initial evidence for putative traits associated within these identified regions. These findings were supported by the results of ontology enrichment analyses. The results reported here will stimulate further research and promote breeding in the future by allowing for the targeted introduction of novel allelic diversity into elite wheat breeding pools. Significance Statement: Utilizing genetic diversity stored in genebanks is essential to cope with future challenges and to ensure breeding progress; here, we provide new insights into genomic regions associated with allelic diversity that are absent from elite wheat, as well as the genomic regions targeted by breeding activities so far. These results provide insights into the genomic signatures of selection and how beneficial alleles can be introduced from plant genetic resources into elite breeding pools.